A novel hydrogen peroxide sensor based on Ag nanoparticles decorated polyaniline/graphene composites. Issue 37 (11th June 2015) - Li, Shan; Xiong, Jianxin; Shen, Jingsong; Qin, Yong; Li, Juan; Chu, Fuqiang; Kong, Yong; Deng, Linhong
ABSTRACT A novel electrochemical sensor based on Ag nanoparticles (AgNPs) decorated polyaniline/graphene composites (PANI/G) is developed, which can be used for sensitive determination of H2O2. For the construction of the H2O2 sensor, polyaniline (PANI) is first electrodeposited on the surface of graphene (G) to form PANI/G, and then horseradish peroxidase (HRP) loaded on AgNPs (HRP/AgNPs) is immobilized on to the PANI/G. H2O2 can be catalyzed by HRP to generate current response which can be significantly enhanced by AgNPs, and thus the PANI/G based sensor can be utilized for the detection of H2O2. Under the optimized conditions, the proposed H2O2 sensor exhibits wide linear response to H2O2 concentration ranging from 0.25 to 2.25 mM with a detection limit of 0.03 mM (signal‐to‐noise ratio of 3), and it also shows high selectivity and reproducibility. The method is simple and cost‐effective, and can be a promising candidate as the sensitive sensing platform for H2O2. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42409.